Hypoxia‐stimulated ATM activation regulates autophagy‐associated exosome release from cancer‐associated fibroblasts to promote cancer cell invasion. Issue 11 (20th September 2021) - Xi, Lei; Peng, Meixi; Liu, Shuiqing; Liu, Yongcan; Wan, Xueying; Hou, Yixuan; Qin, Yilu; Yang, Liping; Chen, Shanchun; Zeng, Huan; Teng, Yong; Cui, Xiaojiang; et al.
Abstract: Cancer‐associated fibroblasts (CAFs) as a predominant cell component in the tumour microenvironment (TME) play an essential role in tumour progression. Our earlier studies revealed oxidized ATM activation in breast CAFs, which is independent of DNA double‐strand breaks (DSBs). Oxidized ATM has been found to serve as a redox sensor to maintain cellular redox homeostasis. However, whether and how oxidized ATM in breast CAFs regulates breast cancer progression remains poorly understood. In this study, we found that oxidized ATM phosphorylates BNIP3 to induce autophagosome accumulation and exosome release from hypoxic breast CAFs. Inhibition of oxidized ATM kinase by KU60019 (a small‐molecule inhibitor of activated ATM) or shRNA‐mediated knockdown of endogenous ATM or BNIP3 blocks autophagy and exosome release from hypoxic CAFs. We also show that oxidized ATM phosphorylates ATP6V1G1, a core proton pump in maintaining lysosomal acidification, leading to lysosomal dysfunction and autophagosome fusion with multi‐vesicular bodies (MVB) but not lysosomes to facilitate exosome release. Furthermore, autophagy‐associated GPR64 is enriched in hypoxic CAFs‐derived exosomes, which stimulates the non‐canonical NF‐κB signalling to upregulate MMP9 and IL‐8 in recipient breast cancer cells, enabling cancer cells to acquire enhanced invasive abilities. Collectively, these results provide novel insights into the role of stromal CAFs in promoting tumour progression and reveal a new function of oxidized ATM in regulating autophagy and exosome release.